Universal Filter Using Single Commercially Available IC: LT1228 - Surapong Siripongdee; Winai Jaikla (My University, 2017)
In electrical and electronic engineering, the filter is very importance circuit. A voltage-mode three inputs single output second-order multifunction filter is presented in this paper. The proposed filter is based on RLC parallel circuit. The main active element is the commercially available IC from Linear Technology Inc, LT1228. The filter consists of single LT1228, single resistor and two capacitors. Five output second-order filter responses, namely band-pass (BP), band-stop (BS), high-pass (HP), low-pass (LP) and all-pass (AP) functions are achieved. Each output response can be selected without component matching condition and the requirement of double gain amplifier. The quality factor and natural frequency can be electronically controlled. PSpice simulation results suing macro model of LT1228 are in close agreement with the theory.
Keywords: Butterworth filter; Constant k filter; Electronic filter; Voltage-controlled filter; RLC circuit; All-pass filter; Electronic filter topology; Analog and Mixed-Signal Circuit Design